Use of ketamine in refractory depression in an adolescent patient: Case report - Ríos Restrepo, Juan David (2025)
Refractory depression is defined as a depressive disorder that does not respond to psychotherapy and two periods of pharmacological management. During adolescence, depression may have different manifestations than in adults, with therapeutic interventions based on the same premise but with variations for each age group. The prevalence of refractory depression is showing a progressive increase, a reason for which the search for more effective management is fundamental. In the midst of the initiatives to address it, the use of ketamine has been proposed, and several authors have detailed different therapeutic doses, duration of treatment and adverse effects. We present the case of a patient with long-term depression, who had undergone multiple therapeutic interventions, without symptomatic control, and who is currently receiving a ketamine regimen with promising results.